A realistic view on heat reuse from direct free air-cooled data centres - Markeby Ljungqvist, Hampus; Risberg, Mikael; Toffolo, Andrea; Vesterlund, Mattias (Energy Conversion and Management: X, 2023)
This paper examines the opportunities to reuse excess heat from direct free air-cooled data centres without incorporating heat pumps to upgrade the heat. The operation of a data centre in northern Sweden, Luleå, was simulated for a year. It was established that heat losses through the thermal envelope and from the humidification of the cooling airflow influenced the momentary energy reuse factor, iERF, with up to 7%. However, for the annual energy reuse factor, ERF, the heat losses could be neglected since they annually contributed to an error of less than 1%. It was shown that the ideal heat reuse temperature in Luleå was 13, 17, and 18 °C with an exhaust temperature of 30, 40 and 50 °C. The resulting ERF was 0.50, 0.59 and 0.66, meaning that a higher exhaust temperature resulted in potentially higher heat reuse. It could also be seen that raising the exhaust temperature lowered the power usage effectiveness, PUE, due to more efficient cooling. Using heat reuse applications with different heat reuse temperatures closer to the monthly average instead of an ideal heat reuse temperature for the whole year improved the ERF further. The improvement was 11–31% where a lower exhaust temperature meant a higher relative improvement. Validerad;2023;Nivå 2;2023-11-15 (hanlid); Full text license: CC BY